Fundamentall and clinical aspects of the use of natural estrogens in the composition of modern combiened hormonal contraception - Лизнева, Д. В.; Синицына, А. И. (REPRODUCTIVE ENDOCRINOLOGY, 2012)
This review presents recent data on the specifics aspects of the pharmacokinetics, metabolism and biological effects of natural estrogens used in combined oral contraceptives.